2023
DOI: 10.1109/tnsre.2022.3217571
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Limb Motor Assessment With Corticomuscular Coherence of Multiple Muscles During Ankle Dorsiflexion After Stroke

Abstract: Motor impairment after stroke is generally caused by damage to the neural networks that control movement. Corticomuscular coherence (CMC) is a valid method to analyze the functional connectivity of the corticospinal pathway between the cerebral cortex and muscles. However, current studies on CMC in stroke patients only focused on the upper limbs. The functional connectivity between the brain and lower limbs in stroke patients has not been well studied. Therefore, twelve stroke patients and fifteen healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…Fang et al found the CMC value was significantly lower in stroke patients than that in healthy controls in beta and lower gamma bands during reaching movements [58]. Our previous research also had similar results, and we also found there was a significant positive correlation between CMC and lower limb Fugl-Meyer Assessment [40]. In patients with hemiplegia, the increase of CMC was accompanied by the recovery of motor function, so cTBS may provide strategies for the rehabilitation of hemiplegia patients.…”
Section: Effect Of Ctbs On Cmc Of Contralateral Hemispheresupporting
confidence: 85%
See 2 more Smart Citations
“…Fang et al found the CMC value was significantly lower in stroke patients than that in healthy controls in beta and lower gamma bands during reaching movements [58]. Our previous research also had similar results, and we also found there was a significant positive correlation between CMC and lower limb Fugl-Meyer Assessment [40]. In patients with hemiplegia, the increase of CMC was accompanied by the recovery of motor function, so cTBS may provide strategies for the rehabilitation of hemiplegia patients.…”
Section: Effect Of Ctbs On Cmc Of Contralateral Hemispheresupporting
confidence: 85%
“…Use MATLAB 2021a (MathWorks, Inc., Natick, MA, United States) to preprocess sEMG signals. Firstly, 20-250 Hz fourth-order Butterworth bandpass filter was used to filter the original sEMG signals [39,40]. The mean baseline was then subtracted from the sEMG data.…”
Section: Preprocessing Of Eeg and Semgmentioning
confidence: 99%
See 1 more Smart Citation
“…The EMG signal was filtered within the range of 20-200 Hz, 34 and the mean absolute amplitude of the filtered EMG was also calculated as a feature of the 10-s segment. The CMC values were determined to measure the linear synchronization between ECoG and EMG signals across the seven frequency bands, 35 with values ranging between 0 and 1, which provided insights into the degree of coherence between the two signals. 36 A normalization procedure was employed to normalize the indices on a scale of 0-1 to reduce errors.…”
Section: Visual Scoring Criteriamentioning
confidence: 99%
“…Various methods, such as corticomuscular coherence (CMC) [7], have been used in studying interactions among neurophysiological signals. The CMC method can reflect frequency interactions among signals but may not reflect the direction of internal information flow [8].…”
Section: Introductionmentioning
confidence: 99%